FINANCIAL MANAGEMENT PLANNING OF MARGOMULYO VILLAGE FUNDS FROM THE PERSPECTIVE OF SAMIN TEACHINGS TO REALIZE SUSTAINABLE ACCOUNTABILITY - Sulistyowati, Rina; Anggapratama, Reza; Rama Prasetya, Nanda ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2025)
This research aims to explore the Samin culture in relation to the planning and management of village funds in Margomulyo Village, from the perspective of Samin teachings, with the goal of achieving sustainable accountability. The research method employed in this study is a qualitative approach, utilizing a case study design. Data collection techniques include observation, interviews, and documentation. Meanwhile, the data analysis technique employs an interactive analysis model that encompasses data reduction, data presentation, and conclusion. Furthermore, data triangulation was used to validate the data. The results of the study show that the planning of village fund financial management, which includes deliberation to determine priority scales, community participation, preparation of village financial management planning (RPJMDes, ‘RKPDes, and ‘APBDes), planning mechanisms in village’ financial’ management, as well as transparency, has been implemented in accordance with Samin teachings. The implications of this study contribute to the body of knowledge in public sector accounting, and, practically, this research can serve as a reference for policy-making related to village fund management planning, based on local culture, specifically the Samin teachings. Implications Technologically, the research results can be utilized in designing a village information system based on local culture, for example, the APBDes dashboard, which includes the values of honesty (transparency), patience (deliberation process), and narimo (reward fairness), so that it is in line with the social character of the village.